Analisis Kredit Macet pada Koperasi Sekolah Menengah Kejuruan - Cynthia Marisa; Puji Muniarty (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2020)
Abstract - A cooperative is an institution or organization in conducting savings and loans in the form of money and goods so that the cooperative members can prosper. Still, from the results of interviews with the head of the cooperative of SMKN 1 Kota Bima, it turns out that there are still many members of the cooperative who do not pay loans or credit bills continuously according to the agreed credit, this will have an impact on the financial condition of the cooperative to provide further credit to its members, so this research aims to determine how much bad credit is in the cooperative of SMKN 1 Kota Bima for the 2014-2019 period. For the sample in this study, the authors used financial reports for the last six years, namely from the 2014-2019 period. The data used in this study uses financial report data in the form of insufficient credit data and total loans; the data used are secondary. The method used is the one-sample t-test (one party test). Where the SMKN 1 Kota Bima cooperative cannot be said to be good because the Non-Performing Loans (NPL) in 2015 amounted to 2.72, 2016 amounted to 1.41, 2017 amounted to 0.75, and 2019 amounted to 0.59 because a good NPL is by criteria, which must be less than 0.05 or 5% of the standard criteria, the same thing can also be seen from the acquisition of lousy credit values ​​from 2015 to 2019 which has been fluctuating, this is because many members of the cooperative did not pay credit installments on time even though contracted the credit agreement is clearly stated that the member will pay for the credit following a mutually agreed decision. Keywords: NPL (Non-Performing Loan), Cooperative, Loan